An augmented reality application for studying atomic orbitals : orbitário - Trindade, Jorge (2004)
"Virtual environments seem to facilitate the formation of correct conceptual models. The main contributing factor is interaction. Augmented reality is a new sort of virtual reality with a new form of interaction. We present Orbitário, an augmented reality application for studying atomic orbitals."